Correlation between self-esteem, coping difficulties, self-efficacy, and illness symptoms towards supported education for students with psychiatric disabilities - Yahaya, Azizi; Ramli, Jamaludin; Yahaya, Noordin; Goh, Siew Yen (2010)
The study examine the need for Supported Education for students with psychiatric disabilities studying at higher education in Johor, Malaysia and to identify the relationships between elements of Supported Education existing in the lives of these students and their current performances. Participant were 30 students from Permai hospital and Sultanah Aminah hospitaj studying in higher education in the state of Johore. As HP and HSA are the only two government hospitals with psychiatric facilities in Johore, the sample was thus recruited from HP and HSA. Low level of coping difficulties faced by these students; high level of SEd elements existing in their lives; high level of self-esteem, moderate level of school self-efficacy; and low level of illness symptoms/symptomatology. The findings showed that higher education students with psychiatric disabilities are academically capable. The strong associations between coping difficulties and current performances imply very clearly that the coping difficulties of these students affect their performances (which is a probable reason for the high college attrition rate among such population).